ELEMENTE DE ARHITECTURĂ TRADIȚIONALĂ ÎNTR-UN FOND DOCUMENTAR INEDIT: RĂSPUNSURILE LA CHESTIONARUL II. CASA AL MUZEULUI LIMBII ROMÂNE - BERINDEI, Cosmina-Maria (Studia Universitatis Babeș-Bolyai Historia Artium, 2021)
Elements of Traditional Architecture in a Unique Documentary Fund: The Replies to The Romanian Language Museum’s 2nd Questionnaire. The House. The present paper’s aim is to demonstrate the scientific importance of the traditional architecture elements preserved in the documentary fund created during the inter-war period at the Romanian Language Museum; the fund is the result of the indirect linguistic survey led by Sextil Pușcariu. The survey included eight thematic questionnaires, the second of which – called The House – recorded the entire vocabulary and knowledge about the culture of building and housing. As the most complex, the 2nd Questionnaire. The House had 489 questions, from the general ones regarding social aspects of housing, to the most detailed ones about the choosing of the site and a minute description of each of the building stages and techniques used by the community. Tributary to „Wörter und Sachen” („Words and Things”) German methodology at the beginning of the 20th century, which claimed that the study of words – to establish their etymology and history – should be done in close connection to the study of artefacts and their cultural lives, Sextil Pușcariu encouraged the correspondents to the Museum’s surveys to illustrate their replies, offering, thus not only linguistic information, but also drawings, no matter how primitive. The 439 replies to the 2nd Questionnaire. The House coming from all the Romania’s regions after Great Union gathered graphical representations of the housing which were and are at the same time ethnographical proof from the beginning of the 20th century, unique through their genuine expressiveness. Thus, the manuscripts include over 2500 graphical representations among which numerous well-done drawings illustrating the most spread house type in the village, but also gates or wells. At the same time, certain drawings minutely show techniques of vernacular construction, systems used for the closing of doors and windows, or whole traditional households with all their elements, from the main buildings to the outbuildings, fences, gates, fountains, fodder storehouses or livestock. This paper demonstrates these unique documents’ importance to the understanding of the housing universe and rural architecture during the inter-war period, emphasizing their value as a useful resource for the contemporary specialists from various domains, from linguists – for whom the documentary fund was created – to anthropologists and ethnographers, but also to specialists from landscape architecture, creative industry or engineering focused on the knowledge of traditional building techniques.